Analisis dan Perancangan Sistem Informasi di SMA Negeri 1 Sambuara Kecamatan Essang Selatan Kabupaten Kepulauan Talaud Berbasis Website - Agustina J Larinse; Oktavini Udang; Yulita Sirinti Pongtambing; Eliyah Acantha M Sampetoding; Meike Tabaru (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Website Design, Information Systems, Information, SMA Negeri 1 Sambuara Essang, Talaud SMA Negeri 1 Sambuara, South Essang District, Talaud Islands Regency is one of the educational institutions that must also manage the data to facilitate information for both the school and the community. Based on the observations, the information management system for SMA Negeri 1 Sambuara still use input system manually, e.g. school profiles, student data, teacher data, and lesson schedule information. The public can only find the information out regarding schools and Teaching & Learning Activities (KBM) by visiting the school directly. This research aims to find out the problem before building an Information System at SMA Negeri 1 Sambuara Based on a Website, it is hoped that this system can facilitate socialization or promote the school to the wider community by using the website. From the results of this discussion, it can be concluded that; this system will make it easier for the school to provide information about student data to visitors or the public, and this system can also make it easier for visitors or the public to find information about student data without knowing distance and time. Comparison of the old system and the new system i.e. The old system is still done manually, while the new system has been carried out in a computerized system, the old system is not efficient and effective, while the new system is the opposite. In the new system, students can input their data directly into the system.